THE ROLE OF ENGLISH IN THE STANDARDIZATION OF TOURIST TERMS IN UZBEK PRACTICE (Scientific journal of the Fergana State University, 2025)
This article explores the role of English in standardizing tourist terms in Uzbekistan. An analysis of how English-derived terms have entered the Uzbek language, their adaptation and their impact on the development of the country in the field of tourism is carried out. The article also discusses how English anglicisms are perceived by experts in the field of turistics and the general public, their functional role and the problems that arise in the field, in particular, difficulties in generalizing and translating terms. As a result, recommendations for standardization of terminology in the field of tourism are given and ways to improve Uzbekistan's competitiveness in the international tourism market are indicated.